2009
DOI: 10.1111/j.1095-8312.2008.01173.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic structure of Anogeissus dhofarica (Combretaceae) populations endemic to the monsoonal fog oases of the southern Arabian Peninsula

Abstract: Anogeissus dhofarica (Combretaceae) is an endemic tree of the monsoon affected coastal mountains of the southern Arabian Peninsula, being the character species of the Hybantho durae-Anogeissetum dhofaricae association, a drought deciduous, monsoon forest community found only in the Dhofar region of southern Oman and the eastern Al-Mahra region of south-east Yemen. Due to the steep precipitation gradient from the centre to the edges in this monsoon affected area, A. dhofarica is found in two different habitat t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 58 publications
(106 reference statements)
0
12
0
Order By: Relevance
“…Meister et al (2006 dated the main split between the western distribution areas of J. areysiana (corresponding to the distribution area of R. s. yemenicola) and the south-eastern distribution areas in Yemen and Oman (corresponding to the patchy distribution area of R. s. simonyi) to 0.8-1.8 Mya. Although a dating has been not possible in the present work, the common pattern is striking and strongly indicates ancient habitat fragmentation due to cycles of aridification during the Pleistocene (Oberprieler et al 2009). …”
Section: Ancient Habitat Fragmentationmentioning
confidence: 68%
See 1 more Smart Citation
“…Meister et al (2006 dated the main split between the western distribution areas of J. areysiana (corresponding to the distribution area of R. s. yemenicola) and the south-eastern distribution areas in Yemen and Oman (corresponding to the patchy distribution area of R. s. simonyi) to 0.8-1.8 Mya. Although a dating has been not possible in the present work, the common pattern is striking and strongly indicates ancient habitat fragmentation due to cycles of aridification during the Pleistocene (Oberprieler et al 2009). …”
Section: Ancient Habitat Fragmentationmentioning
confidence: 68%
“…Importantly, the stronger population structure found in R. s. simonyi may be highly linked to the monsoonal fog oases of the southern Arabian Peninsula (Oberprieler et al 2009), because the larval host plant of R. simonyi is only found in these patches similar to other plants species like Justicia areysiana (Meister et al 2005(Meister et al , 2006 and Euclea schimperi (Meister et al 2008). Meister et al (2006 dated the main split between the western distribution areas of J. areysiana (corresponding to the distribution area of R. s. yemenicola) and the south-eastern distribution areas in Yemen and Oman (corresponding to the patchy distribution area of R. s. simonyi) to 0.8-1.8 Mya.…”
Section: Ancient Habitat Fragmentationmentioning
confidence: 99%
“…However, empirical research has documented contradictory genetic effects of habitat loss and fragmentation especially on long-lived tree species [ 18 ]. That is to say, some studies have shown adverse effects of habitat loss and fragmentation on the genetic diversity and structure of various tree species [ 19 - 22 ] whereas others did not find genetic effects of forest fragmentation [ 23 - 25 ]. The absence of genetic effects of fragmentation among long-lived tree species is most likely due to the recent history of human disturbance and fragmentation events whose genetic effects will only be reflected after multiple generations which might not have been accounted for by some researchers [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…The precipitation and cooling effect provided by the summer monsoon isa driving force for the unique and diverse vegetation of the Dhofar Mountains [32,[43][44][45]. The areas most affected by the summer monsoon are the southwest facing slopes of the Dhofar Mountains, particularly the escarpment cliffs on Jabal al Qara and al Qamar.…”
Section: Discussionmentioning
confidence: 99%